Indonesia's Abundant Wealth from The Baduy Culture - Saragih, Febrianta Lidia; Turnip, Putri Kumala; Simbolon, Basbon (Future Science, 2023)
The Baduy community is a tribe originating from the interior of Banten and living in Kenakes Village, Leuwidar, Lebak, Banten. The Baduy community is a tribe that has not been affected by modern culture and still obeys the rules that apply in their place of residence. The Baduy people do not want to accept a new culture and deliberately alienate themselves from outside life to avoid modernization as a way for them to respect their ancestors so that the balance and harmony of the universe can be maintained. The Baduy tribe is divided into two parts, namely the Inner Baduy and Outer Baduy who live in crowded settlements. The striking difference between the two tribes is that the Inner Baduy people have not been touched by technology and modernization at all, while the Outer Baduy people.